PENGARUH PARTISIPASI MASYARAKAT, PENGGUNAAN SISTEM KEUANGAN DESA, KOMPETENSI PENDAMPING DESA SERTA KOMITMEN PEMERINTAH DAERAH TERHADAP KEBERHASILAN PENGELOLAAN DANA DESA - I Putu Julianto; Gusti Ayu Ketut Rencana Sari Dewi (Universitas Pendidikan Ganesha, 2019)
Research aims to understand The Influence Of Public Participation, The Use Of The Villages Financial System, A Companion Competence Of The Villages And Local Government Commitment To Successful Of Village Funds Management. The research is quantitative research using types of data on obtained from the questionnaire and primary is measured using likert scales. The population in this study using the whole chief of village officer, treasurer, the villages officials, as well as the operator siskeudes in Buleleng Regency. The sample collection Technique use probability sampling that is simple random sampling. The criteria of the sample in this study is the whole chief of village officer, treasurer, the villages officials, as well as the operator siskeudes in Buleleng Regency as many as 224 people. Data analysis techniques in this study using multiple linear regression analysis with SPSS version 23. The results of the research indicated that the variable public participation (x1) influence positively and significant to successful of village funds management, the use of the village financial system (x2) influence positively and significant to successful of village funds management, variable a companion competence of the villages (x3) influence positively and significant to successful of village funds management, and the variable of local government commitment (x4) influence positively and significant to successful of village funds management.